Characterization of an Anti-CD70 Half-Life Extended Bispecific T-Cell Engager (HLE-BiTE) and Associated On-Target Toxicity in Cynomolgus Monkeys. (18th May 2022) - Harper, Tod; Sharma, Amy; Kaliyaperumal, Sarav; Fajardo, Flordeliza; Hsu, Katie; Liu, Lily; Davies, Rhian; Wei, Yu-Ling; Zhan, Jinghui; Estrada, Juan; Kvesic, Majk; Nahrwold, Lisa; et al.
Abstract: Bispecific T-cell engager (BiTE) molecules have great potential to treat cancer. Nevertheless, dependent on the targeted tumor antigen, the mechanism of action that drives efficacy may also contribute to on-target/off-tumor toxicities. In this study, we characterize an anti-CD70 half-life extended BiTE molecule (termed N6P) which targets CD70, a TNF family protein detected in several cancers. First, the therapeutic potential of N6P was demonstrated using in vitro cytotoxicity assays and an orthotopic xenograft mouse study resulting in potent killing of CD70 + cancer cells. Next, in vitro characterization demonstrated specificity for CD70 and equipotent activity against human and cynomolgus monkey CD70 + cells. To understand the potential for on-target toxicity, a tissue expression analysis was performed and indicated CD70 is primarily restricted to lymphocytes in normal healthy tissues and cells. Therefore, no on-target toxicity was expected to be associated with N6P. However, in a repeat-dose toxicology study using cynomolgus monkeys, adverse N6P-mediated inflammation was identified in multiple tissues frequently involving the mesothelium and epithelium. Follow-up immunohistochemistry analysis revealed CD70 expression in mesothelial and epithelial cells in some tissues with N6P-mediated injury, but not in control tissues or those without injury. Collectively, the data indicate that for some target antigens such as CD70, BiTE molecules may exhibit activity in tissues with very low antigen expression or the antigen may be upregulated under stress enabling molecule activity. This work illustrates how a thorough understanding of expression and upregulation is needed to fully address putative liabilities associated with on-target/off-tumor activity of CD3 bispecific molecules.